Forest management affects ecosystem functioning (predation and herbivory) but not ecosystem constancy: A comparative study across four forest ecosystems around the world - Hernández-Agüero, Juan A. (Elsevier BV, 2025)
Forest management can affect both the functioning and stability of ecosystems. Constancy and persistence are key factors that contribute to the overall stability of an ecosystem. These factors can be highly variable and change across forest ecosystems. We studied the effects of forest management on the strength of resource–consumer interactions (bird predation and insect herbivory) as important measures of ecosystem functioning, as well as on their constancy in time in four different forested regions globally. Within each region, we selected (i) three heavily managed or plantation forests, and (ii) three urban/peri-urban forests or urban plantings, and paired each of them with pristine/semi-natural forests. Bird predation was estimated using plasticine caterpillars of different colors. Chewer, galler, and miner herbivory on leaves were estimated for 15 plants (shrubs and trees) per study site. Constancy was quantified as the invariability of both predation and herbivory during a period of three (exceptionally two) years. We found no consistent responses of either predation or herbivory to forest management practices across study regions. Bird predation was higher in urban/peri-urban forests than in pristine/semi-natural forests in Patagonian and boreal forest, with intermediate levels of predation in managed or plantation forests. These differences might be explained by the increase of resource availability during the winters and by the higher abundances of generalist predators due to increase of temperatures (i.e., urban heat effect), for those regions where winter temperatures could be a limiting factor. Chewing insect herbivory was lower in urban/peri-urban forests, probably due to the exclusion of certain herbivores in response to warming and the higher predation pressure relative to pristine forests. No differences were found in other types of herbivory, indicating that effects of urbanization are guild-specific. In addition, we consistently found no effects of forest management practices on predation invariability and herbivory, thereby demonstrating the high constancy of ecosystem functioning to different forest management practices across regions. These findings advance our knowledge of the generalized effects of forest management on ecosystem functions and stability by establishing a connection between the ecology and management and conservation of plantations and natural forests.